2017 American College of Rheumatology Guideline for the Prevention and Treatment of Glucocorticoid‐Induced Osteoporosis. Issue 8 (6th June 2017) - Buckley, Lenore; Guyatt, Gordon; Fink, Howard A.; Cannon, Michael; Grossman, Jennifer; Hansen, Karen E.; Humphrey, Mary Beth; Lane, Nancy E.; Magrey, Marina; Miller, Marc; Morrison, Lake; Rao, Madhumathi; et al.
Abstract : Objective: To develop recommendations for prevention and treatment of glucocorticoid‐induced osteoporosis (GIOP). Methods: We conducted a systematic review to synthesize the evidence for the benefits and harms of GIOP prevention and treatment options. The Grading of Recommendations Assessment, Development and Evaluation methodology was used to rate the quality of evidence. We used a group consensus process to determine the final recommendations and grade their strength. The guideline addresses initial assessment and reassessment in patients beginning or continuing long‐term (≥3 months) glucocorticoid (GC) treatment, as well as the relative benefits and harms of lifestyle modification and of calcium, vitamin D, bisphosphonate, raloxifene, teriparatide, and denosumab treatment in the general adult population receiving long‐term GC treatment, as well as in special populations of long‐term GC users. Results: Because of limited evidence regarding the benefits and harms of interventions in GC users, most recommendations in this guideline are conditional (uncertain balance between benefits and harms). Recommendations include treating only with calcium and vitamin D in adults at low fracture risk, treating with calcium and vitamin D plus an additional osteoporosis medication (oral bisphosphonate preferred) in adults at moderate‐to‐high fracture risk, continuing calcium plus vitamin D but switching from an oral bisphosphonate to another antifracture medication in adults in whom oral bisphosphonate treatment is not appropriate, and continuing oral bisphosphonate treatment or switching to another antifracture medication in adults who complete a planned oral bisphosphonate regimen but continue to receive GC treatment. Recommendations for special populations, including children, people with organ transplants, women of childbearing potential, and people receiving very high‐dose GC treatment, are also made. Conclusion: This guideline provides direction for clinicians and patients making treatment decisions. Clinicians and patients should use a shared decision‐making process that accounts for patients' values, preferences, and comorbidities. These recommendations should not be used to limit or deny access to therapies.